Characterization and electrocatalytic applications of metallophthalocyanine-single walled carbon nanotube conjugates - Mugadza, Tawanda (Rhodes University, Faculty of Science, Department of Chemistry, 2011)
Metallophthalocyanine-single walled carbon nanotube conjugates were successfully synthesized and applied in the electrochemical characterizations of pesticides (amitrole and diuron) and 2-mercaptoethanol (2-ME). The formation of conjugates was confirmed through the use of the following analytical techniques: UV-vis, FTIR, Raman and XRD spectroscopies, atomic force and transmission electron microscopies and voltammetry. Chemically linking SWCNT to MPcs created platforms that offered efficient transfer of electrons and this was confirmed through electrochemical impedance studies (EIS) and voltammetry as shown by lower Î”Ep values observed in conjugates. Carboxy carrying MPcs have very poor electron transfer kinetics (both tetrasubstituted and low symmetry), but the presence of SWCNTs activates their catalysis. All electrochemical studies were done at pH 4. Cyclic voltammetry, rotating disk linear sweep voltammetry, chronoamperometry and EIS were used in the electrochemical characterization of 2-ME and the pesticides on poly-Ni(OH)TAPc and MPc-SWCNT modified glassy carbon electrodes (GCEs). High Tafel slopes were observed for the pesticides relative to 2-ME, an indication of the passivating nature of their oxidation products. However, conjugates showed very high resistances to passivation and were easily regenerated by shaking in methanol. Improved catalysis of the conjugates is also indicated by the high catalytic rate constants for the analytes, observed on these electrodes. Conjugates of low symmetry MPcs with SWCNTs gave the highest catalytic rate constants, confirming better catalysis on these electrode surfaces. The nature of SWCNT functionalization also affected catalysis, with amine functionalized SWCNTs inducing better catalytic properties into the MPcs than carboxylic acid terminated CNTs. The presence of amine functionalized SWCNTs activates the catalysis of non-catalytic carboxy-carrying MPcs and this is more pronounced in conjugates of tetrasubstituted MPcs relative to those of low symmetry Pcs. Ethylene amine (EA) functionalized SWCNTs reduced redox overpotentials of the MPcs more than the phenyl-amine (PA) functionalized counterparts. Poly-NiTAPc was successfully converted to poly-Ni(OH)TAPc through cyclisation in pH 4 buffer and showed very good catalytic properties towards diuron, relative to the former.
Keywords: Phthalocyanines; Pesticides; Nanotubes; Electrocatalysis; Electrochemistry; Transmission electron microscopy